Effects of Prolonged Exposure to Hydrogen Peroxide on Expiratory Peak Flow - Suparwati, Komang Tri Adi; Jaya, I Putu Prisa; Paramurthi, I.A Pascha; Dharmayanti, Cokorda Istri (Mulawarman International Conference on Tropical Public Health, 2025)
Background : The bleaching process on the ibung to get a brighter color requires a hydrogen peroxide dyeing process. In this process, artisans are directly exposed to hydrogen peroxide vapor. The duration of exposure to hydrogen peroxide results in respiratory disturbances that affect the peak expiratory flow. Objective : This study aims to determine the relationship between the length of exposure and the duration of exposure in ibung craftsmen Research Methods/ Implementation Methods: This research is a type of quantitative research with an observational analytical method. The design of this study uses a cross-sectional approach with a sample of 50 people who meet the inclusion and exclusion criteria. The Peak Flow Meter instrument is used to assess the peak current of expiratory flow of the ibung craftsman against hydrogen peroxide exposure. Statistical analysis was carried out using descriptive and chi-square tests Results : Based on the chi-square test, the results were obtained on the meaningful relationship between the length of work and the peak flow of expiration with the value of p = 0.000 and a meaningful relationship was found between the duration of work and the peak flow of expiration with the value of p = 0.043 Conclusion/Lesson Learned : There is a relationship between exposure to hydrogen peroxide to the peak expiratory current in Ibung craftsmen, so it is expected that Ibung craftsmen use PPE (personal protect equipment when working to reduce exposure to hydrogen peroxide